2000
DOI: 10.1017/s0031182099005582
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the role of red foxes in Echinococcus multilocularis transmission in the urban area of Sapporo, Japan

Abstract: In order to assess the infection risk of alveolar echinococcosis among urban residents of Sapporo, the capital of Hokkaido, Japan, a survey was conducted on fox distribution in the urban area and on the prevalence of Echinococcus multilocularis among the foxes. The fox distribution, evaluated from fox footprints left on the snow in parks and woodlands, and from locations of fox carcasses recorded by the Sapporo municipality, was concentrated along the border of the urban area and in the southwestern part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 6 publications
5
44
0
1
Order By: Relevance
“…The urban cycle of the parasite is now documented in Zurich and Geneva (Switzerland), Stuttgart (Germany), Copenhagen (Denmark), Sapporo (Japan), Nancy, Annemasse and Pontarlier (France), and Calgary (Canada) (Hofer et al, 2000;Tsukada et al, 2000;Deplazes et al, 2004;Fischer et al, 2005;Robardet et al, 2008;Catalano et al, 2012;Comte et al, 2013). A general pattern that seems to emerge is a decrease in E. multilocularis prevalence in foxes according to the following gradient: rural periphery/residential peri-urban area/urban centre.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
See 1 more Smart Citation
“…The urban cycle of the parasite is now documented in Zurich and Geneva (Switzerland), Stuttgart (Germany), Copenhagen (Denmark), Sapporo (Japan), Nancy, Annemasse and Pontarlier (France), and Calgary (Canada) (Hofer et al, 2000;Tsukada et al, 2000;Deplazes et al, 2004;Fischer et al, 2005;Robardet et al, 2008;Catalano et al, 2012;Comte et al, 2013). A general pattern that seems to emerge is a decrease in E. multilocularis prevalence in foxes according to the following gradient: rural periphery/residential peri-urban area/urban centre.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
“…Tsukada et al (2000) analysed the distribution of foxes by detecting fox footprints in winter in 130 parks and woodlands evenly distributed within the city and sampled fox faeces in approximately 19 fox dens in the area. Significantly more footprint-positive parks and woodlands were located in the peripheral area (47.6%) than in the urban centre (22.9%), and copro-ELISA positive faeces were collected in 11 out of 19 dens, with only one located in the urban centre.…”
Section: Urban and Peri-urban Environmentsmentioning
confidence: 99%
“…In Europe, the red fox is the main source of environmental contamination (Deplazes & Eckert, 2001). Recent studies have shown the presence of E. multilocularis in red fox in various cities: Copenhagen (Kapel & Saeed, 2000), Geneva (Fischer et al, 2005), Prague (Martinek et al, 2000), Stuttgart (Romig et al, 1999), ZĂŒrich (Hofer et al, 2000) in Europe, Sapporo (Tsukada et al, 2000) and Otaru (Yimam et al, 2002) in Japan. The prevalence among urban foxes was lower than among suburban or rural foxes.…”
Section: Introductionmentioning
confidence: 99%
“…They may also infect humans with rabies or alveolar echinococcosis by the tapeworm Echinococcus multilocularis (Uraguchi et al 2009). The first case of alveolar echinococcosis infection in a Sapporo resident was reported in 1997 (Tsukada et al 2000). The public health issues such as preventing risk of zoonosis associated with the presence of wildlife in cities are the focus of much research, as is the drive for extensive control measures (Bateman and Fleming 2012).…”
Section: Development Of Sapporo Citymentioning
confidence: 99%